1992
DOI: 10.1039/jm9920200443
|View full text |Cite
|
Sign up to set email alerts
|

Non-linear optical studies of nickel dithiolene complexes

Abstract: The third-order optical non-linearity, x ( ~) , linear absorption coefficient, CI, and the ratio of the real to imaginary parts of f 3 ) have been measured at 1.06 pm for a range of nickel dithiolene complexes with absorption bands between 0.77 and 1.06 pm. From these data the non-linear refractive index, n2, and the device-based figure of merit, W ( =Ansat/aA), were calculated. W was found to exceed 2 for materials with absorption maxima below 0.8-0.85 pm. The non-linear refractive index of a poly(methy1 meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
26
0
1

Year Published

1996
1996
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(28 citation statements)
references
References 10 publications
0
26
0
1
Order By: Relevance
“…-Previous investigations of the nonlinear optical properties of these complexes have focused on third-order susceptibilities at 1.06 m for applications in all-optical signal processing [26][27][28][29]. For a few complexes, the two-photon absorption at 1.06 m has been measured, since nonlinear absorption is detrimental to alloptical signal processing; low 2PA coefficients were observed [30,31].…”
Section: R Familymentioning
confidence: 99%
“…-Previous investigations of the nonlinear optical properties of these complexes have focused on third-order susceptibilities at 1.06 m for applications in all-optical signal processing [26][27][28][29]. For a few complexes, the two-photon absorption at 1.06 m has been measured, since nonlinear absorption is detrimental to alloptical signal processing; low 2PA coefficients were observed [30,31].…”
Section: R Familymentioning
confidence: 99%
“…The -electron delocalization in conjugated systems can also contribute to the ultrafast response capability and large third-order nonlinearity. Recently, some of these complexes possessing good second-order [5,6] and third-order [7][8][9][10][11] NLO properties have been reported. In this paper, a dmit 2salt: bis(tetraethylammonium)bis(1,3-dithiole-2thione-4,5-dithiolato)cadium was synthesized.…”
Section: Introductionmentioning
confidence: 99%
“…As special π-electron conjugated systems and charge-transfer complexes, they have been used as highly electrical conductors and superconductors [1][2][3][4][5]. Recently, researchers have initiated the investigation on the nonlinear optical (NLO) properties of those coordination complexes, and have found that the π-electron delocalization and charge transfer in the systems can also contribute to an ultrafast optical response capability and large third-order NLO effects [6][7][8][9][10][11][12]. These make them into potential candidates in the NLO domain.…”
Section: Introductionmentioning
confidence: 99%